A Preliminary Study on the Use of Rice Husk-Based Smoke Powder for Meatball Preservatives - Muhammad Faisal; Hera Desvita; Yusya Abubakar; null Azwar (Journal of Food Quality)
This study examines the use of smoke powder derived from rice husks as a preservative for chicken meatballs. Rice husks were pyrolyzed in a slow pyrolysis reactor at the temperatures of 300°C (T1), 350°C (T2), and 400°C (T3) to produce liquid smoke. Each of the liquid smoke was distilled at 190°C and then converted into smoke powder by spray drying method. The smoke powder’s feasibility as a meatball preservative was examined by total plate count (TPC), total volatile base (TVB), most probable number (MPN) test of E. coli, and organoleptic (aroma, texture, and color) tests. The results showed that the TPC and TVB increased with storage time. At the storage time of 76 hours, the meatballs were no longer suitable for consumption as the TPC had exceeded the minimum limit. In meatballs with T3 smoke powder at 72-hour storage, the number of colonies was 6.87 × 104 CFU/g, indicating the TPC value has not exceeded the threshold yet. The TVB test showed that up to 72 hours of storage, the meatballs remained fresh with a TVB value of less than 0.20 mgN/g. The result of the organoleptic test also showed that meatballs could last for 72 hours. The MPN test, on the other hand, revealed that the E. coli was still permissible after 68 hours of preservation.